Pharmacological treatment of primary chronic venous disease: Rationale, results and unanswered questions - Perrin, M.; Ramelet, Anne-Sylvie (2011)
Aim: The aim of this article was first to review the complex pathophysiological mechanisms responsible for symptoms and signs of primary chronic venous disease (CVD) that allow the identification of targets for pharmacological treatment. The results of CVD treatment with venoactive drugs (VADs) were emphasised and presented in the form of recommendations. The last section raises key questions to be answered to improve protocols for good clinical trials and to draw up future guidelines on these agents. Methods: The literature has been reviewed here using PubMed and Embase. Results: Venous hypertension appears to underlie all clinical manifestations of primary CVD. Inflammation is key in wall remodelling, valve failure and subsequent venous hypertension. Changes in the haemodynamics of veins are transmitted to the microcirculation, resulting in capillary alteration leading to oedema, skin changes and eventually venous ulceration. Venous symptoms may be the result of interplays between pro-inflammatory mediators and nerve fibres located in the venous wall. Therefore, venous inflammation constitutes a promising therapeutic target for pharmacological intervention, and some available VADs could attenuate various elements of venous inflammation. Based on recent studies, reviews and guidelines, tentative recommendations for the use of VADs were proposed and strong recommendations were given to two of them (micronised purified flavonoid fraction and oxerutins). Conclusion: VADs should be accorded a better role in the management of CVD. However, larger and more definitive clinical trials are needed to improve the existing recommendations. © 2010 European Society for Vascular Surgery. Published by Elsevier Ltd. All rights reserved.